If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -12 = 5x + -9 Reorder the terms: -12 + 10x = 5x + -9 Reorder the terms: -12 + 10x = -9 + 5x Solving -12 + 10x = -9 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -12 + 10x + -5x = -9 + 5x + -5x Combine like terms: 10x + -5x = 5x -12 + 5x = -9 + 5x + -5x Combine like terms: 5x + -5x = 0 -12 + 5x = -9 + 0 -12 + 5x = -9 Add '12' to each side of the equation. -12 + 12 + 5x = -9 + 12 Combine like terms: -12 + 12 = 0 0 + 5x = -9 + 12 5x = -9 + 12 Combine like terms: -9 + 12 = 3 5x = 3 Divide each side by '5'. x = 0.6 Simplifying x = 0.6
| ax+bx=d | | 70x+70=70 | | 2w+8x-13y+4w+4x+8y= | | 21x^5y^2+14x^2y^3= | | 2(9x+1)=3(5x-8)+25 | | 22(2w-3)=6w | | 2x^2+(10p+1)x+5=0 | | 2(2z-3)=-3(z+5) | | 12b^2-11b+2=0 | | 5.12t+12.42(30t)=500 | | 10p^2(p+1)=5 | | 9x-6w+5x+6y+5y+3w= | | 3(x-3)=12+x | | -3x+8=1-4x | | 6x+3=2x-21 | | 10x^2-18x+12=0 | | 4+7=-9 | | 4x-6=12x-30 | | 3x+2y=-14 | | (-5+x)/2=3 | | -2(x)-(3)=12+(x) | | 5(x+3)+6x=136 | | -2x-(3)=12+(x) | | 4m+12=112 | | 20a+14b+2c+5c-4b-2a= | | 0.12x+0.02x=50000 | | 7+7(x)=8+6(x) | | a+5*2=9 | | 3m+12=112 | | 11x=6x-15 | | 4x^2-2x=6x^2-2(x^2-x) | | x^4+7x^3+11x^2-7x-12=0 |